Avaliação em língua estrangeira (inglês) no acesso ao ensino superior : o ENEM em discussão - Rauber, Bárbara Battistelli (2012)
Inferences based on the results of language tests have been used to make decisions about people s lives because tests work as a gateway at important moments related to education, employment and moving from one country to another (MCNAMARA, 2000). In this study, we aimed at discussing the inclusion of an English test in the ENEM entrance examination in Brazil. This test evaluates the reading ability in English as a Foreign Language (EFL). Its use in the Brazilian educational system was introduced without the development and publication of specifications that are a central and crucial part of a test construction process. Test specifications should include information related to the theoretical framework underlying the test and the level of understanding expected from test-takers (ALDERSON; CLAPHAM; WALL, 1995). From this perspective, we conducted an interpretative research (MOITA LOPES, 1994) based on documents (LANKSHEAR; KNOBEL, 2008) in order to understand the construct that underlies the ENEM English test. The documents that contributed to the data analysis were the English Curricular Guidelines for Brazilian Secondary Schools and the Guidelines for ENEM 2009, which are the documents that direct the development of the current version of ENEM. The results obtained from the analysis of the 2010 and 2011 ENEM English tests show that the assessment of the EFL reading ability is operationalized primarily through the decoding of texts by test-takers, which originates from a narrow concept of language (SCARAMUCCI, 1995). Based on this, we believe that the ENEM English test does not allow test-takers to read between the lines, as suggested by the English Curricular Guidelines. The results also show that the competence and the skills presented by the Guidelines for ENEM 2009 are not implemented in the ENEM English test. Furthermore, the results suggest that the development of this test should be reconsidered by the test writers, starting with the design and publication of specifications that are coherent with the contemporary theories that guide the process of EFL teaching, learning and assessment.